Measuring the Indicators of Happiness Index in Malang City - Ummu Sahdiah Sahlan (Journal of International Conference Proceedings (JICP), 2020)
This study was conducted to analyse the magnitude of indicators of happiness index in Malang City society. The purpose is to observe the indicators that have the lowest and the highest values. Measuring the indicators in this study is based on indicators of happiness index from Badan Pusat Statistik (Central Agency on Statistics) in 2017. There are 19 indicators which are divided into three dimensions, which are Life Satisfaction, Affection, and Meaning in Life Dimensions. Determination of indicator values is using Exploratory Factor Analysis (EFA) method to determine the weights of each indicator. The results showed that the highest indicator of Happiness Index is family harmony of life satisfaction dimension and the lowest indicator is feeling not worried and not depressed of affection dimension.